2008
DOI: 10.3233/ves-2008-18105
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular function in families with inherited autosomal dominant hearing loss

Abstract: The inner ear contains the developmentally related cochlea and peripheral vestibular labyrinth. Given the similar physiology between these two organs, hearing loss and vestibular dysfunction may be expected to occur simultaneously in individuals segregating mutations in inner ear genes. Twenty-two different genes have been discovered that when mutated lead to non-syndromic autosomal dominant hearing loss. A review of the literature indicates that families segregating mutations in 13 of these 22 genes have unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In our study, 19 mutated deafness genes associated with vestibular phenotypes were identified, and AD was the most common inheritance pattern. Variations in COCH, MYO7A, TECTA, WFS1, and POU4F3 with AD inheritance patterns and CDH23, GJB2, and SLC26A4 with AR inheritance patterns are associated with vestibular phenotypes [6,9,[13][14][15][28][29][30][31]42,43]. However, other genes such as DIAPH1, PMXL2, EYA4, GRHL2, KCNQ4, MYH9, and NLRP3 with AD inheritance patterns and MPZL2, MYO15A, and WFS1 with AR inheritance patterns have not been reported regarding their association with vestibular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, 19 mutated deafness genes associated with vestibular phenotypes were identified, and AD was the most common inheritance pattern. Variations in COCH, MYO7A, TECTA, WFS1, and POU4F3 with AD inheritance patterns and CDH23, GJB2, and SLC26A4 with AR inheritance patterns are associated with vestibular phenotypes [6,9,[13][14][15][28][29][30][31]42,43]. However, other genes such as DIAPH1, PMXL2, EYA4, GRHL2, KCNQ4, MYH9, and NLRP3 with AD inheritance patterns and MPZL2, MYO15A, and WFS1 with AR inheritance patterns have not been reported regarding their association with vestibular phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the clinical characteristics of the vestibular phenotypes of the identified genes. Although vestibular phenotypes with hereditary hearing loss have been reported previously [9,, most of these studies enrolled few patients or described vestibular symptoms/results of vestibular function tests that focused on specific genes causing hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations